The Effectiveness of Information Technology-Based Education on Self-Efficacy of Stroke Patients: A Scoping Review - Widayanto, Doto; Handayani, Fitria; Djohan, Andrew (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Stroke patients often experience changes in body structure, form, and function, which can lead to a decrease in self-efficacy. Individuals living with chronic illness require social support, health education, guidance, and coping strategies to manage their condition. One of the challenges faced by stroke patients is the limited access to in-person support services. Delivering care through alternative modes such as video, computer, or telephone has the potential to overcome some of these barriers. This review aimed to examine the effectiveness of information technology-based educational interventions on the self-efficacy of stroke patients. This study employed a scoping review framework. Literature searches were conducted using databases including Scopus, CINAHL, ScienceDirect, ProQuest, and PubMed. The keywords used were “stroke” AND “education” AND “self-efficacy”, limited to publications from the past 10 years. Articles were written in English and of the randomized controlled trial type. A total of nine articles were reviewed, which reported the use of technology-based media such as telephone, video, virtual reality, and computer devices in the follow-up care of stroke patients at home. The findings indicate that the use of information technology is effective in improving self-efficacy, health literacy, and the quality of life of stroke patients.